2013
DOI: 10.1002/ijc.28452
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and breast cancer risk: A meta‐analysis of observational studies

Abstract: Studies on the association of short or long sleep duration with breast cancer risk have reported inconsistent results. We quantitatively assessed this association by conducting a meta-analysis based on the evidence from observational studies. In April 2013, we performed electronic searches in PubMed, EmBase and the Cochrane Library to identify studies examining the effect of sleep duration on breast cancer incidence. The odds ratio (OR) was used to measure any such association in a randomeffects model. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 40 publications
1
50
0
2
Order By: Relevance
“…Recent meta-analyses of these data, while noting substantial heterogeneity in results, concluded that the evidence to date does not support an association between sleep duration and overall cancer risk [9,11,13]. Other than for breast and colorectal cancers, these meta-analyses, however, could not consider other site-specific risks due to the fact that there has not been more than one original study published for the other specific cancer sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses of these data, while noting substantial heterogeneity in results, concluded that the evidence to date does not support an association between sleep duration and overall cancer risk [9,11,13]. Other than for breast and colorectal cancers, these meta-analyses, however, could not consider other site-specific risks due to the fact that there has not been more than one original study published for the other specific cancer sites.…”
Section: Discussionmentioning
confidence: 99%
“…Although two systematic reviews have supported an association between duration of sleep and risk of cancer [13,14], a review by Lu et al refuted an overall association [15], not excluding the existence of a positive association in specific cancer subtypes. Although most studies that assessed the association between SDB and cancer supported a positive association [16][17][18][19][20], evidence contrary to this also exists [21].…”
Section: Introductionmentioning
confidence: 93%
“…For studies that used multiple short-sleep-duration groups, we selected the most extreme group for quantifying the effects of short sleep [34,35], the mode being 5 h or less ( Table 1). The same applied to long sleep, with the most common category being 9 h or more (Table 1).…”
Section: Definition Of 'Short' and 'Long' Sleep Durationmentioning
confidence: 99%